Contestation Of Jihad And Social Media Narrative: A Case Study Of Isis - Mohd Kaslan, Umi Nur Zahidah (2021)
This study set to look for the differences between the two terms in order to unravel the hugely contested concept of jihad that often misused to generalize the action of one party which ultimately contributes to the growing xenophobic sentiment towards Islam and its followers.